Comparing the efficacy of a dentifrice containing 1.5% arginine and 1450 ppm fluoride to a dentifrice containing 1450 ppm fluoride alone in the management of primary root caries - Souza, M.L.R; Cury, J.A; Tenuta, L.M.A; Zhang, Y.P; Mateo, L.R; Cummins, D; Ellwood, R.P (Journal of dentistry, 2013)
Abstract Objective To compare the efficacy of a new dentifrice containing 1.5% arginine and 1450 ppm fluoride to a positive control dentifrice containing 1450 ppm fluoride alone in arresting and reversing primary root caries lesions in adults. Study design A total of 3779 subjects from Piracicaba, Säo Paulo, Brazil were screened; 284 had at least one leathery primary root caries lesion and were eligible for the study. The new dentifrice contained 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride, as sodium monofluorophosphate; the matched positive control dentifrice contained 1450 ppm fluoride. One lesion for each subject was selected for inclusion in the study and was examined at baseline, 3 and 6 months. Results A total of 253 subjects completed the study with 129 of 144 subjects included in the final statistical analysis for the test dentifrice and 124 of 140 for the positive control. The mean age of subjects was 45.7 (±9.19) years and 56.5% were female. After 6 months product use, 70.5% of root caries lesions improved for subjects using the arginine-containing dentifrice compared to 58.1% for subjects using the positive control. The difference in the number of root caries lesions becoming hard in the two groups was statistically significant ( p = 0.038). Conclusion A new dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride, as sodium monofluorophosphate, provided statistically significantly superior efficacy in arresting and reversing active root caries lesions in adults compared to a matched positive control dentifrice containing fluoride alone.